Kelas Kemahiran al-Quran ke Arah Pembangunan Generasi al-Quran di Malaysia - Mohd Faisal Mohamed; Wan Hasmah Wan Mamat; Moh Yakup Zulkifli Mohd Yusoff (Jurnal Forum Tarbiyah, 2012)
In generating Al Quran-literate society, the government through the Ministry of Education has implemented specific programs of Al Quran Learning Classes. At the beginning, this program was applied in the National Secondary School since 1986. Started in 2002, a special program of the Al Quran Learning Class was implemented in Kelas Aliran Agama (Religious Streams) in schools under the Ministry of Education. Therefore, this article will discuss matters related to the implementation of specific programs of the Al Quran Learning Class in developing the character of a Muslim individual needs. In addition, a number of issues and matters relating to the implementation of this program are presented.